A Novel Surgical Classification for Extremity and Pelvic Hemophilic Pseudotumors: The PUMCH Classification. (19th April 2023) - Li, Ziquan; Xiao, Ke; Chang, Xiao; Zhou, Xi; Bian, Yanyan; Zhang, Baozhong; Liu, Yong; Gao, Peng; Feng, Bin; Weng, Xisheng
Abstract : Background: A hemophilic pseudotumor (HPT) is a rare and challenging complication of hemophilia for which there is no classification system that provides uniformity of descriptions or that can be used to guide management. We have developed such a classification based on anatomical site, HPT severity, and corresponding surgical treatment. Methods: The PUMCH (Peking Union Medical College Hospital) classification was developed on the basis of clinical manifestations and imaging features. Extremity and pelvic HPTs were divided into 4 types and 6 subtypes according to anatomical site and whether or not there was destruction of adjacent bone. Associations between the PUMCH classification and surgical treatment, preoperative comorbidities, operative time, intraoperative bleeding, and postoperative complication rates were analyzed. Results: Forty-five patients with 53 HPTs that were treated at PUMCH between December 2005 and October 2021 were included. The mean age at the time of surgery was 35.4 ± 11.9 years, and the median follow-up duration was 60.3 months. Twenty-eight HPTs were classified as type I (13 IA, 7 IB, 8 IC); 3, as type II; 6, as type III; and 16, as type IV. All 20 type-IA and IB HPTs were treated with excision, and the 3 type-II HPTs were treated with curettage and bone grafting. Fourteen type-IV pelvic HPTs underwent excision, 2 of which needed concomitant pelvic reconstruction. Six type-IC HPTs and 1 type-III HPT underwent excision and osseous reconstruction. Amputation was required for 1 type-IC and 3 type-III HPTs. Type-IC HPTs had the longest mean operative time (194.3 ± 28.2 minutes) and the greatest intraoperative bleeding (2, 000 mL [interquartile range, 1, 100 to 3, 000 mL]). Postoperative infection was more common in patients with type-III (50.0%) and type-IC (28.6%) HPTs, but not significantly so. Conclusions: The PUMCH classification is based on the anatomic pathology and surgical strategy for HPTs. The classification of HPTs corresponds to surgical outcomes, and may be helpful for decision-making regarding their surgical treatment. Level of Evidence: Prognostic Level IV . See Instructions for Authors for a complete description of levels of evidence.